1965
DOI: 10.3758/bf03343201
|View full text |Cite
|
Sign up to set email alerts
|

Visual stimulus complexity and food vs. food alone as rewards for rats

Abstract: Abstract111 three experiments, normally reared hooded rats were exposed to a T maze with the same black-white pattern in each arm and were later tested with the pattern in one arm changed. Half the Ss received food for entering the unchanged arm and halffor entering the changed arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1967
1967
1968
1968

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The findings from Trials 1 and 31, that the majority of Ss entered the temporally changed arm, support the usefulness of using temporal changes in pattern as a basis for determining choice behavior. They are consistent with previous data (Earl, Franken, & May, 1967;May et al, 1965;Musselman, 1963) and with the theoretical analysis suggested by .…”
Section: Testsupporting
confidence: 93%
“…The findings from Trials 1 and 31, that the majority of Ss entered the temporally changed arm, support the usefulness of using temporal changes in pattern as a basis for determining choice behavior. They are consistent with previous data (Earl, Franken, & May, 1967;May et al, 1965;Musselman, 1963) and with the theoretical analysis suggested by .…”
Section: Testsupporting
confidence: 93%
“…The failure to obtain a decrease in response to temporal complexity over days, either as a result of rewarded trials or repetition, is attributed to the method of pacing temporal stimulus complexity. Sackett, Keith-Lee, & Treat (1963) and May, Beauchamp, & Pollock (1965) have shown that rats will choose a visually complex stimulus over food in a T maze. One problem with both studies is the failure to adequately familiarize Ss with the presence of food reward prior to the introduction of the complex stimulus.…”
mentioning
confidence: 99%